2017
DOI: 10.1038/s41598-017-04734-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression in Honeybee Queens by the Neonicotinoids Thiacloprid and Clothianidin

Abstract: Queen health is crucial to colony survival of honeybees, since reproduction and colony growth rely solely on the queen. Queen failure is considered a relevant cause of colony losses, yet few data exist concerning effects of environmental stressors on queens. Here we demonstrate for the first time that exposure to field-realistic concentrations of neonicotinoid pesticides can severely affect the immunocompetence of queens of western honeybees (Apis mellifera L.). In young queens exposed to thiacloprid (200 µg/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 70 publications
1
51
1
Order By: Relevance
“…She can also be influenced by different environmental stressors during development, either through exposure to biotic or abiotic stressors in the colony environment or specifically via the quality or quantity of royal jelly she receives [29][30][31][32][33]. After maturation, a queen may face different stresses during her nuptial flights [33][34][35] and after the onset of oviposition inside her colony [36][37][38][39][40][41][42][43]. Environmental stresses can cause negative consequences for the developing queens such as substantial reduction in survival, and reduce queen emergence [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…She can also be influenced by different environmental stressors during development, either through exposure to biotic or abiotic stressors in the colony environment or specifically via the quality or quantity of royal jelly she receives [29][30][31][32][33]. After maturation, a queen may face different stresses during her nuptial flights [33][34][35] and after the onset of oviposition inside her colony [36][37][38][39][40][41][42][43]. Environmental stresses can cause negative consequences for the developing queens such as substantial reduction in survival, and reduce queen emergence [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…Neonicotinoids target nicotinic acetylcholine receptors (nAChRs) which they bind to and thus excite; this can result in paralysis, convulsions and death (Matsuda et al, 2001). Controlled exposure experiments using honeybees and bumblebees have shown that exposure at comparable concentrations to those found in nectar and pollen can have sublethal effects on learning and memory (Siviter, Koricheva, Brown, & Leadbeater, 2018;Stanley, Smith, & Raine, 2015), cognition and problem solving (Baracchi, Marples, Jenkins, Leitch, & Chittka, 2017;Samuelson, Chen-Wishart, Gill, & Leadbeater, 2016;Williamson & Wright, 2013), motor function (Drummond, Williamson, Fitchett, Wright, & Judge, 2016;Williamson, Willis, & Wright, 2014), foraging performance (Gill & Raine, 2014;Henry et al, 2012;Stanley, Russell, Morrison, Rogers, & Raine, 2016), navigation abilities (Fischer et al, 2014) and the immune system (Brandt, Gorenflo, Siede, Meixner, & Büchler, 2016;Brandt et al, 2017;Di Prisco et al, 2013). Despite the growing interest in the link between neonicotinoid exposure and toxicity to bees, we know little about the molecules and genes through which neonicotinoid action is mediated, or whether neonicotinoids may also affect "off-target" processes that are not mediated by nAChRs.…”
mentioning
confidence: 99%
“…In honeybees and bumblebees, sublethal neonicotinoid exposure at concentrations comparable to those found in nectar and pollen affects the immune system negatively, resulting in a reduction of hemocyte density, encapsulation response, and antimicrobial activity [9,10,198,199]. Similar to vertebrates, exposure to neonicotinoids also induces oxidative stress by alteration in retinoid metabolism [200].…”
Section: Pollutants: Pesticidesmentioning
confidence: 99%